Pendidikan Multikultural di Lembaga Pendidikan Islam (Konsep dan Implementasi di Madrasah Ibtidaiyah Al-Ichsan Surabaya) - Dewi Ixfina, Ficky; Syamsudin, Syamsudin; Lailatul Fitriani, Siti (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
Indonesia is a diverse nation with various ethnicities, languages, traditions, and social classes, even in the religious aspect. The fact is that Indonesians have problems figuring out how to manage multiculturalism to minimize conflict caused by the term